Calculation and Evaluations for n+64, 66, 67, 68, 70, natZn Reactions. (2nd September 2018) - Hu, Jiaqi; Xu, Yongli; Han, Yinlu
Abstract: All cross sections, angular distributions, energy spectra, and double-differential cross sections are consistently calculated and analyzed for n+ 64, 66, 67, 68, 70, nat Zn reactions over the incident neutron energy range from 0.001 to 200 MeV. The optical model, preequilibrium and equilibrium reaction theories, and the distorted wave Born approximation theory are used. Theoretical calculated results are compared with the existing experimental data and the evaluated results in JEFF-3.2 and JENDL-4.0.